Four Year trend of antimicrobial susceptibility of methicillin-resistant Staphylococcus aureus in a tertiary care hospital, Lahore - Faiqa Arshad; Sidrah Saleem; Romeeza Tahir; Ayesha Ghazal; Aneela Khawaja; Shah Jahan (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the susceptibility pattern of methicillin-resistant staphylococcus aureus to different antibiotics. Method: The descriptive study was conducted at the Microbiology Department of the University of Health Sciences, Lahore, Pakistan, from August 2016 to July 2019, and comprised staphylococcus aureus samples that were processed and identified using colony morphology on blood agar, gram stain, catalase, coagulase and deoxyribonuclease testing. Screening for methicillin-resistant staphylococcus aureus was done using cefoxitin disc 30µg and oxacillin disc 1?g. Antimicrobial susceptibility was tested using the modified Kirby-Bauer disc diffusion method in line with the Clinical and Laboratory Standards Institute guidelines 2019. Data was analysed using SPSS 24. Results: Of the 2704 strains processed, 402(14.86%) were found to be methicillin-resistant staphylococcus aureus. Of them, 204(50.74%) were recovered from pus, while 10(2.48%) were recovered from urine. All 402(100%) isolates were sensitive to vancomycin and linezolid, and resistant to penicillin, followed by erythromycin 306(76.11%) and sulfamethoxazole/ trimethoprim 295(73.38%). Overall, lower resistance was seen with doxycycline 145(36.06%) and clindamycin 160(39.80%). Inducible clindamycin resistance was seen in 142(35.23%) isolates. Conclusion: An efficacious susceptibility pattern of methicillin-resistant staphylococcus aureus was seen with vancomycin and linezolid, moderate susceptibility with doxycycline and clindamycin, while high resistance was observed for penicillin, erythromycin and trimethoprim/sulfamethoxazole. Key Words: Antimicrobial resistance, Antibiotic susceptibility, Methicillin-resistant staphylococcus aureus, MRSA. Continuous...